Wnt Signaling in the Breast: From Development to Disease - Abreu de Oliveira, Willy Antoni; El Laithy, Youssef; Bruna, Alejandra; Annibali, Daniela; Lluis, Frederic (Frontiers in Cell and Developmental Biology, 2022)
The Wnt cascade is a primordial developmental signaling pathway that plays a myriad of essential functions throughout development and adult homeostasis in virtually all animal species. Aberrant Wnt activity is implicated in embryonic and tissue morphogenesis defects, and several diseases, most notably cancer. The role of Wnt signaling in mammary gland development and breast cancer initiation, maintenance, and progression is far from being completely understood and is rather shrouded in controversy. In this review, we dissect the fundamental role of Wnt signaling in mammary gland development and adult homeostasis and explore how defects on its tightly regulated and intricated molecular network are interlinked with cancer, with a focus on the breast.